Manfaat Pelatihan Tematik Manajemen Pakan Terhadap Perubahan Prilaku Milenial dalam Agribisnis Peternakan di Kabupaten Lombok Timur: Mashur - Mashur Mashur (Pusluhtan, 2023)
The development of the agricultural sector is facing quite serious problems, namely the continuing increase in the number of livestock farmers in smallholder livestock businesses who are in adulthood, and the decreasing number of young farmers. This study aims to determine changes in millennial behavior in the field of livestock agribusiness through thematic training in animal feed management. The research was conducted in September 2019 at the Garuda Independent Rural Agriculture Training Center (P4S), Kalijaga Timur Village, Aikmel District, East Lombok Regency, West Nusa Tenggara Province. The research method used is a descriptive method, which describes changes in the behavior of the millennial participants as a result of the Thematic Animal Feed Management training. Changes in behavior that are measured are the level of knowledge, skills and attitudes (follow-up action plan) of participants before (pretest) and after training (posttest). The number of respondents was 20 training participants. The research results show that the level of millennial knowledge has increased by 12.75 percent regarding animal feed management in the development of livestock agribusiness. Millennials' level of knowledge of feed training materials increased by 17.50 percent. The number of millennials who have skills in preparing rations and mixing feeds has also increased. Based on the follow-up training plan, the most interest from millennials in the development of livestock agribusiness is laying hens and laying ducks. This thematic animal feed management training is able to change millennial behavior in livestock agribusiness.